HISTORIOGRAPHY OF SOVIET CENSORSHIP: MAIN TRENDS OF THE RESEARCH STUDIES AND CONCEPTS OF CENSORSHIP - Sėdaitytė, Edita (Knygotyra, 2017)
There are many definitions of Soviet censorship in different scientific research studies. Censorship is a complex phenomenon. It is not only a control of the public sector (press and mass media). Censorship covers a multitude of areas – from the public to the private spheres of life, from institutional, regulated control to internal self-censorship. Due to these reasons, studies of censorship are relevant to various scientific fields. The aim of this research is to analize the main concepts of Soviet censorship and trends of these research studies. In order to achieve this aim, scientific works, surveying Soviet censorship from various perspectives aspects were analyzed. The goal was to distinguish the main trends of research studies and to understand focusing on the context to which Soviet censorship is related. The analysis of various concepts of censorship and other concepts used to describe this phenomenon has allowed to highlight the differences between scientists’ attitudes towards this phenomenon. The research-based analysis concluded that the main trends of research studies of Soviet censorship are as follows: 1. censorship as one of the features of Soviet occupation; 2. censorship as a part of Soviet culture; 3. censorship as one of KGB’s work methods; 4. censorship as a specific connection between creative artists and the Soviet system; 5. censorship as a part of press and publishing history; 6. censorship as part of daily work of memory institutions. In the studines that are focused exclusively on censorship, most of the analysis is oriented towards censorship as an institution (Glavlit) and its work methods. Censorship in memory institutions is presented as “cleaning” of library collections, a destruction of books or development of restricted (special) collections. When analyzing censorship, Lithuanian researchers present this phenomenon as one-sided totalitarian control. Foreign authors quite often base their research on the theories of P. Bourdieu or M. Foucault and present censorship both as a means of control and as a power that defines culture and communication. The concept of soviet censorship in these research studies is also defined in quite a few ways, for example, as a means of control or as a restriction of press and mass media, as a boundary or information barrier. Censorship can be analyzed as an institution, as a work method of that institution (Glavlit) or as one of many features of soviet mass communication. There is a lack of research studies that might give rise to different theories and present a more complex view of soviet censorship.
Keywords: soviet censorship; historiography; sovietology